Case report: Asymmetric bilateral deep brain stimulation for the treatment of pantothenate kinase-associated neurodegeneration in a patient: a unique case of atypical PKAN with a novel heterozygous PANK2 mutation - Hong, Guo; Zhang, Zhongwen; Wang, Peiyi; Li, Guoyang; Zhang, Wenli; Zou, Huahui; Luo, Xiaoguang (Frontiers in Human Neuroscience, 2024)
Pantothenate kinase-associated neurodegeneration (PKAN) is a rare autosomal recessive hereditary neurodegenerative disorder, usually caused by mutations in the pantothenate kinase 2 (PANK2) gene. We report a young female patient with atypical PKAN, harboring a novel heterozygous PANK2 mutation, diagnosed through clinical imaging and genetic analysis. The patient presented with dystonia and motor dysfunction after onset, but early brain MRI showed normal findings. Due to progressive symptom deterioration, her MRI was reevaluated and the characteristic “eye of the tiger” sign was identified. Further genetic testing revealed that she was a carrier of two heterozygous PANK2 mutations, one being a known pathogenic variant and the other unknown. Given the patient’s clinical presentation, progressive symptoms, and poor response to medication, we boldly attempted asymmetric bilateral deep brain stimulation (abDBS). Postoperative outcomes showed significant symptom improvement. This study suggests that early brain MRI in PKAN patients may not exhibit typical radiological features, leading to potential diagnostic omissions. Furthermore, it highlights the potential therapeutic effect of abDBS in atypical PKAN, particularly in patients with novel heterozygous PANK2 mutations. Asymmetric bilateral deep brain stimulation may represent a promising treatment approach.